The Gender of Virtual Worlds: Gender Relationships, Cultural Practices and Symbolisms in Prayers of a Virtual Community - Foulidi, Xanthippi; Papakitsos, Evangelos C. (American Journal of Social Sciences and Humanities, 2020)
This research aims to enrich the existing theoretical framework for the relationship between Folklore and the Internet, focusing on gender relations, cultural practices and symbolisms that exist in virtual communities. Initially, the contemporary international and national literature is studied that addresses these issues and then the methodology of online ethnography is applied with a gender perspective to a specific religious virtual community. The moderate participation of one of the authors in this religious virtual community had the purpose of gathering more information about women, members of this digital community. The main research question of this study was whether there is a gender perspective in a virtual community or not. The members of this virtual community pointed out that there is no gender discrimination or discrimination against women, and no gender inequality in the members of their community. Therefore, this study also clarifies processes and gendered behaviors that are shaped by it, but also highlights predominant beliefs, ideologies, behaviors, social actions, internalized patterns of behavior, as well as instruments and expressive features, etc. that exist in them. The results of the research help to fill bibliographic gaps and produce a new theory of the relation between folk culture, gender and new technologies.